2020
DOI: 10.1111/jace.17162
|View full text |Cite
|
Sign up to set email alerts
|

Low‐temperature sintering of magnesium aluminate spinel doped with manganese: Thermodynamic and kinetic aspects

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…Figure a shows that, before and after DSC sintering of the undoped samples, both Mn 3+ and Mn 4+ are present, which is in agreement with the literature but with a particularly higher concentration of Mn 4+ (a feature claimed by Reddy et al to have a possible relation to the improved cycling performance). No significant differences in terms of the Mn 3+ -to-Mn 4+ ratio were observed when comparing samples before and after sintering, which indicates the absence of oxidation state changes during the test …”
Section: Resultsmentioning
confidence: 89%
“…Figure a shows that, before and after DSC sintering of the undoped samples, both Mn 3+ and Mn 4+ are present, which is in agreement with the literature but with a particularly higher concentration of Mn 4+ (a feature claimed by Reddy et al to have a possible relation to the improved cycling performance). No significant differences in terms of the Mn 3+ -to-Mn 4+ ratio were observed when comparing samples before and after sintering, which indicates the absence of oxidation state changes during the test …”
Section: Resultsmentioning
confidence: 89%
“…This would imply that Al‐rich samples can better accommodate these residual stresses. A possible explanation for this is the localization of the excess Al similar to ionic dopants which can pin the movement of grain boundaries in grain growth experiments at elevated temperatures, either by kinetics of thermodynamics 28,44–47 . Chiang and Kingery have shown that excess Al can impact the coarsening behavior of non‐stoichiometric magnesium aluminate by modifying grain boundary chemistries 22,48 .…”
Section: Resultsmentioning
confidence: 99%
“…A possible explanation for this is the localization of the excess Al similar to ionic dopants which can pin the movement of grain boundaries in grain growth experiments at elevated temperatures, either by kinetics of thermodynamics. 28,[44][45][46][47] Chiang and Kingery have shown that excess Al can impact the coarsening behavior of non-stoichiometric magnesium aluminate by modifying grain boundary chemistries. 22,48 The change in load accommodation at room temperature observed here is somehow equivalent to recent works on dopant-engineered grain boundaries in metals [49][50][51] and ceramics.…”
Section: Discussionmentioning
confidence: 99%
“…15 This phenomenon has been observed in various doped nanocrystalline oxide systems, and it is possible Al 3+ ion enrichment at the interfaces may affect Y 2 O 3 densification. 11,[16][17][18][19] Wang et al studied the role of Al 2 O 3 on the sintering of Y 2 O 3 containing small amounts of Tm and Zr. 20 The dopant was effective in improving densification, which was an attribute to activated sintering, a phenomenon observed in other systems such as Bi 2 O 3 -doped ZnO and ZrO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…[1]) and (B) of Al-doped Y 2 O 3 at 15 K/min heating rate for samples coarsened at 750℃ for 15 h after baseline subtraction and deconvolution A survey of the published literature modeling of CMCs has been studied by a n ers. Processes that have been modeled CVD, 17,18 CVI, [19][20][21][22] and Sol-Gel Infiltrat of alumina matrix in eight-harness satin has been studied numerically in Ref. [ proaches used in the above work general ing the flow of a high viscosity resin thr and modeling the chemical reactions and during processing.…”
Section: Methodsmentioning
confidence: 99%